Project-Based Learning Innovations to Improve Students’ Creative Thinking Ability in Chemistry Learning Process Development Courses - M. Dwi Wiwik Ernawati; Minarni; Fatria Dewi; Yusnidar (Universitas Pendidikan Ganesha, 2023)
Project Based Learning model was chosen as a solution found by researchers in the field regarding the low creative thinking ability of students. Project Based Learning model based on projects by observing teacher learning videos downloaded by prospective teacher students and then analyzed together with group friends. This study aims to analyze students' creative thinking skills through a project-based Project Based Learning model by designing RPS and SAP lectures, then implementing them and finally evaluating. This research is class action research, which is conducted in several cycles. Instruments in the form of student activity are observation sheets and evaluation tools in the form of multiple-choice tests to collect data on learning outcomes to see student creativity in analyzing the learning videos. The three instruments are made based on a grid derived from a conceptual framework. The result found broadly speaking, in one cycle there are four common stages, namely: the planning stage, the acting stage, the observation stage, and the reflection stage. Learning is carried out using a project-based learning model. Student activities were observed by observers and recorded (video was made). Based on the results of observations and video recordings, reflection is carried out for planning the next cycle of learning. At the end of each cycle a post-test was held to see the activity data collected by the observation method and the learning outcomes data by the test method.